Efficiency, technological progress and productivity growth of Vietnamese commercial banks in the period 2008–2024: A Malmquist index approach - Dung, Pham Tien; Anh, Dưong Nguyen Hong; Phuong, Trinh Hoang; Vinh, Hoang Xuan (Edelweiss Applied Science and Technology, 2025)
This study evaluates the efficiency and productivity growth of 22 Vietnamese commercial banks over the period 2008–2024 using a non-parametric approach. Applying the output-oriented Malmquist Productivity Index under constant returns to scale (CRS), we decompose total factor productivity (TFP) into efficiency change (EC) and technical change (TC). The results show that EC values remained close to unity for most banks, indicating relatively stable managerial performance. However, TC values varied significantly across institutions, suggesting that technological progress is the primary driver of TFP divergence. Among the 22 banks, only six achieved positive TFP growth, led by NVB, SEAB, and ABB—banks that demonstrated strong adaptability through technical improvements. In contrast, HDB, BIDV, and VPB recorded notable declines in productivity, largely due to lagging technological progress rather than inefficiency. These findings emphasize the critical role of digital transformation and innovation in sustaining long-term productivity. The study contributes updated empirical evidence on banking performance in Vietnam and offers strategic implications for bank executives and policymakers aiming to enhance competitiveness in a rapidly evolving financial environment.